Digital media and digital divides: an exploration of primary school-age children's use of and access to digital media - Potzel, Katrin (Media Education Research Journal, 2024)
The article presents an in-depth analysis of the digital divide regarding children in middle childhood and its implications for educational institutions. It focuses on how children's access to digital media, their media usage, and related skills vary significantly, influenced by socio-economic backgrounds and family environments as well as peer contexts. As basic framework, the article highlights three levels of the digital divide: access to digital media devices and infrastructure, differences in media usage and media-related skills, and the impact of these disparities on formal education. With empirical data from the longitudinal qualitative study ConnectedKids - Socialisation in a Changing Media Environment (ConKids), the article illustrates how the digital divide manifests in the age of primary school. It shows that children's media repertoires and competencies are diverse and influenced by their family environment, leading to varying levels of media literacy and therefore possible influences in educational outcomes. The COVID-19 pandemic further highlighted these disparities, as distance schooling requirements exposed the gap between children's media usage at home and school. The article concludes with challenges for educational institutions deriving from these empirical insights, emphasising the need to consider children's varied media backgrounds and competencies in curriculum development and teaching practices. It suggests that addressing these disparities early in education is crucial for promoting inclusive media literacy and ensuring equal opportunities for digital participation